1998
DOI: 10.1515/cclm.1998.077
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Time and Temperature on Coagulation Analytes in Stored Plasma

Abstract: There is no comprehensive study on the stability of coagulation analytes in plasma. We therefore determined the influence of storage time and temperature on prothrombin time, activated partial thromboplastin time, thrombin time, fibrinogen, factors V and VIII, antithrombin III, protein C and S in plasma from 20 healthy subjects and 20 patients receiving heparin therapy. The stability in plasma, defined as the period during which there was a change of less than 10% from the initial value, was 8 hours for activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
56
3
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 5 publications
14
56
3
4
Order By: Relevance
“…Previous report indicated that APTT measurements were increased at 4˚C while PT measurements were decreased at 4˚C [23]. Similarly, Heil and colleagues [24] demonstrated that APTT samples were stable up to 8 h at either RT or 4˚C, except for those which were on unfractionated heparin therapy. Several studies recommended that PT and APTT determinations may be constant for periods more than currently suggested in NCCLS guidelines [25] [26].…”
Section: Discussionmentioning
confidence: 84%
“…Previous report indicated that APTT measurements were increased at 4˚C while PT measurements were decreased at 4˚C [23]. Similarly, Heil and colleagues [24] demonstrated that APTT samples were stable up to 8 h at either RT or 4˚C, except for those which were on unfractionated heparin therapy. Several studies recommended that PT and APTT determinations may be constant for periods more than currently suggested in NCCLS guidelines [25] [26].…”
Section: Discussionmentioning
confidence: 84%
“…In 1998 Heil et al carried out an influential study that is still the basis for several guidelines and recommendations about coagulation testing [59] . Basically, the authors determined the influence of storage time and temperature on PT, APTT, thrombin time (TT), fibrinogen, factors V and VIII, antithrombin, protein C and S in plasma from healthy subjects and patients receiving heparin therapy.…”
Section: Laboratory Hemostasis Throughout Clinical Chemistry and Labomentioning
confidence: 99%
“…Heil [3] Im Lichte unserer Fragestellung gilt es auch, das Citrat/P/ajwfl-Volumenverhältnis näher zu betrachten. Wir beschrieben für Globalteste jüngst eine Hyperkoagulabilität bei einem Citrat/Blut-Volumenverhältnis von 1:14 und eine Hypokoagulabilität bei einem Verhältnis von unterhalb l: 9, erfolgte die Abnahme in 0,109 mol/1 Natriumcitrat und war der Hämatokrit mit 45 % (0,45) "normal".…”
Section: Statistische Auswertungunclassified
“…Citratplasma für Gerinnungsanalysen war Gegenstand verschiedener Arbeiten der vergangenen Jahre [1][2][3][4][5]. Die Ergebnisse zeigten teilweise deutliche Differenzen, sowohl bei unterschiedlichen Testverfahren als auch bei gleichen Testverfahren mit Reagenzien verschiedener Hersteller [l, 3,4]. In anderen Arbeiten wurde der Einfluß von Über-oder Unterfüllung des Entnahmeröhrchens auf Gerinnungsteste untersucht [5,6].…”
unclassified